Organosolv pulping using oil palm frond: effect of liquor ratio on pulp and paper properties / Muhammad Hanis Ahmad Mahmmud - Ahmad Mahmmud, Muhammad Hanis (2007)
The research was done to identify the effect of pulping and paper properties based on differences liquor ratio which is 1:6, 1:8 and 1:10. Oil palm frond is used in the alkaline organosolv pulping with 180°C cooking temperature and 100 minutes of cooking time. The result showed the increasing of degree of freenes, tensile index and also bust index, while decreasing in bulk and tearing index.